Corporate Social Responsibility Activities that Influence Customer Loyalty of SMEs - Turyakira, Peter K. (International Journal of Business and Management, 2018)
Businesses are increasingly required to address the demands of key stakeholders, in addition to those of shareholders. There is an increasing role of corporate social responsibility (CSR) to large businesses and small and medium enterprises (SMEs) alike. However, research to support the degree of the application of CSR activities to SMEs with respect to customer loyalty is limited. The purpose of this study was to examine the selected CSR activities that impact the customer loyalty of SMEs. A self-administered questionnaire was distributed to selected SMEs in Kampala District, while Structural Equation Modeling was utilised to determine the influence of independent variables on the dependent variable. The study findings revealed that the selected CSR activities (Society-oriented CSR activities, Market-oriented CSR activities and Environmental-oriented CSR activities) positively influence the Customer loyalty of SMEs.
Keywords: Corporate social responsibility factors; Customer loyalty; Small and medium enterprises